2006
DOI: 10.1097/01.aog.0000207677.03235.76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parity on Sexual Function

Abstract: II-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
5
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 14 publications
7
59
5
10
Order By: Relevance
“…), behavioural ones (avoidance intercourse) and cognitive ones (fear, anxiety, etc.).) (Xu et al, 2003;Botros et al, 2006). In our study, while the rates of experiencing dispareunia in postpartum period were found as 20.8% in prenatal period, 22.9% during pregnancy and 35.6% in the first postpartum intercourse, the rate of postpartum dispareunia was detected to be 41.5%.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…), behavioural ones (avoidance intercourse) and cognitive ones (fear, anxiety, etc.).) (Xu et al, 2003;Botros et al, 2006). In our study, while the rates of experiencing dispareunia in postpartum period were found as 20.8% in prenatal period, 22.9% during pregnancy and 35.6% in the first postpartum intercourse, the rate of postpartum dispareunia was detected to be 41.5%.…”
Section: Discussionsupporting
confidence: 42%
“…Sexuality is a natural part of life (Boroumandfar et al, 2010) and one of important determinants of quality of life (Botros et al, 2006). When sexual wellbeing is deteriorated, sexual disfunctions appear.…”
Section: Introductionmentioning
confidence: 99%
“…Caesarian delivery appears to decrease the incidence of dyspareunia in the first 3-6 months but has no further benefit [22]. However, other concomitant factors must be important as mode of delivery was not significant for sexual function in 29 identical twin pairs discordant for mode of delivery [23].…”
Section: Woman's Response To Pregnancymentioning
confidence: 90%
“…La función sexual es un importante indicador de la calidad de vida, el cual esta influenciado por una variedad de factores físicos, psicológicos y sociales (3). Por lo tanto, no debe comprenderse la sexualidad humana sin reconocer de antemano su carácter pluridimensional; es decir, tiene que haber una dimensión personal, individual, donde se expresa el yo del individuo; una dimensión de pareja donde haya una expresión de vivencias, goce, placer o displacer en la pareja; una dimensión familiar donde se manifieste la reproducción y la comunicación filial, así como también una dimensión social donde se exprese comunicación y mandatos sociales (4).…”
Section: Introductionunclassified
“…A pesar que el parto representa un acontecimiento central en la vida reproductiva de una mujer, en términos tantos físicos como psicosociales, este acarrea un impacto potencial en todos los dominios de la función sexual. Diversos estudios han demostrados que las mujeres que han tenido hijos tienen menores puntuaciones en los indicadores auto-reportados de la función sexual, al compararse con las nulíparas, sin embargo se han atribuido más bien a factores psicológicos y sociales que a una lesión del piso pélvico (3).…”
Section: Introductionunclassified